Security and privacy within smart cities - Путник, Ненад; Marković, Jana (Sociološki pregled, 2025)
The global trend of increasing urbanization and expansion of cities in recent decades has caused numerous problems in their functioning. The rapid development of information and communication technologies has emerged as a solution to these problems and led to the emergence of so-called smart cities. A smart city is conceived as a new model of a city that generates and processes enormous amounts of digital data with the aim of optimizing urban infrastructure and improving living conditions. However, the use of new technologies has raised many questions and caused concerns about the way these technologies are used and the possibilities of misuse of collected data. The paper describes the key characteristics of the smart city architecture and analyzes the issues of threats to the security and privacy of citizens opened up by it. The sources and forms of threats to security and privacy in smart cities are numerous, interconnected and require a detailed analysis from a technical-technological, sociological and legal perspective.